Black Women's Liberatory Pedagogies Resistance, Transformation, and Healing Within and Beyond the Academy (Springer International Publishing, 2018)
This interdisciplinary anthology sheds light on the frameworks and lived experiences of black women faculty in the academy. Contributors for this anthology submitted works from an array of academic disciplines and learning environments, inviting readers to bear witness to black women faculty's classroom experiences, as well as their pedagogical approaches both inside and outside of the higher education classroom that have fostered transformative teaching-learning environments. Through this multidimensional lens, the editors and contributors view instruction and learning as a political endeavor aimed at changing the way we think about teaching, learning. and praxis. .